Resolução CSMPF nº 190, de 4 de dezembro de 2018 - Luciano Mariz Maia; Maria Caetana Cintra Santos; Alcides Martins; Hindenburgo Chateaubriand Pereira Diniz Filho; Nivio de Freitas Silva Filho (DMPF-e, Brasília, DF, 15 fev. 2019. Caderno Extrajudicial, p. 1., 2019)
Exclui os artigos 47, 48, 49, 50 e 51 da Resolução CSMPF nº 178, de 5 de setembro de 2017.